On peculiarities of distinguishing similar grammatical concepts - Garbačiauskienė, M. (Psichologija, 1963)
1. Individual peculiarities of thinking are often explained by exceptionally nervous activity. However, the latter does not disclose the specifics of thinking capabilities. It is also necessary to consider the degree of assimilation of the laws of logical thinking.2. Based on the assumption that human social experience, stated in the laws of logic, is assimilated differently by each child depending on his/her outer and inner conditions, the article aims at establishing individual ways of differentiation by comparing them with the logically correct way. The main criterion of righteous differentiation (and generally, comparison) is, firstly, considered as the constant ratio between the differentiation and the operation opposite to it—superposition, because determination of the identity of the compared objects limits and at the same time controls the differentiation process (the difference is determined only inside a certain sameness). Moreover, the degree of assimilation of the laws of logic is also attempted to consider.3. Individual ways of differentiation have been investigated by performing different variants of the declarative experiment, involving 32 students of 6th-8th grades. Each participant of the experiment was given more than 20 tasks—to differentiate similar grammatical concepts. Furthermore, the investigated students were asked by the experiment leader to assess various (mostly wrong) examples of established differences.4. Several ways of differentiation as the most uniform and characteristic to individual members of experiment may be distinguished:a) Placement, i.e. determination of the difference without resorting to objects’ identityb) Stating of the outer differencec) Differentiation based on initial superposition (discerning a common feature)d) Establishing the difference within an essential sameness5. Individual differentiation is presumably anchored when a student’s thought often travels the incorrect path or stops in some earlier, more simplistic stage and, therefore, the action stage of the differentiation process takes place—premature generalization and automation is made.
Keywords: thinking; individual differences; differentiation concepts